Effect of the plastic deformation on the electrochemical behavior of metal coated steel sheets - Sacco, E. A. (2003)
Protective metallic coatings based on Zn or Al-Zn alloys are usually used to protect steel against corrosion. When coated steel sheets are subjected to formed processes, its corrosion behavior is affected due not only to changes of the galvanic coating texture but also of the twins and cracks developed. The aim of the present work was to evaluate the performance of galvanized steel or steel/55%Al-Zn sheets mechanically deformed and exposed to 0.5 M NaCl; 0.5 M NaClO4 and 0.5 M Na2SO4 solutions. Samples built up from commercially available coated steel sheets were uniaxially deformed up to reach an elongation of 1.3, 6.25 and 12.5%. The corrosion behavior of deformed and non-deformed samples was evaluated by means of DC electrochemical techniques. The experimental results allowed to infer that: (1) there were evident differences in the kinetics of the corrosion reactions taking place at the surface of both metallic coatings and (b) such kinetics is a function of the deformation degree as well as of the electrolyte aggressiveness.